Experimental research and computer simulation of face grind-hardening technology - Li, Jianping (Strojniški vestnik, 2013)
The influence of technical parameters on face grind-hardening surface hardness and hardened layer depth were determined by systematic experimental studies on technological parameters, such as grinding methods and grinding parameters, which provides a reference for choosing reasonable parameters in face grind-hardening processing. By FEA simulation of the grinding temperature field using ANSYS software, the variation in temperature at different points on the workpiece surface and the temperature field dynamic states are determined. The simulation results are consistent with the experimental values, which indicates that the simulation method is feasible for studying face grind-hardening.
Keywords: ANSYS software; brusilno utrjanje; čelno brušenje; face grinding; FEA simulation; globina utrjenega sloja; grind-hardening; hardened layer depth; površinska trdota; programska oprema ANSYS; simulacija MKE; surface hardness